USING THE YOU ONLY LOOK ONCE (YOLO) METHOD FOR DETECTING PHYSICAL DISTANCING AND MASKED FACES - Khairul Azman; Muhammad Arhami; Azhar; Zhenyu Cui (PT. Radja Intercontinental Publishing, 2023)
The flow of news regarding the development of Covid-19 has dominated various information channels in Indonesia in the last 2 years, either through print media or digital media. Various types of news related to Covid-19 continue to circulate, including hoax news. One of the hoax news that is widely circulating is news about the Covid-19 vaccine. The rise of information containing hoax news and untrue rumors about the Covid-19 vaccine in society can worsen the pandemic situation. Currently there is no intelligent system capable of classifying hoaxes regarding the Covid-19 vaccine. To maximize prevention of the spread of hoax news about the Covid-19 vaccine and overcome the problems faced, the author designed a classification system for hoax news about the Covid-19 vaccine using a machine learning approach. The system built can classify news using a combination of the Name Entity Recognition (NER) and Backpropagation algorithms. The datasets used are: 600 Covid-19 vaccine news data obtained from the sites https://turnbackhoax.id/ and https://www.kompas.com/ with the keyword